Standard of Proof Required to Issue an Arrest Warrant for Genocide - Carnero Rojo, Enrique (Utrecht Journal of International and European Law, 2011)
At the time of writing this case note, the case against Omar Al Bashir is the only genocide case before the InternationalCriminal Court. So far, the main legal question concerns whether the existence of reasonable grounds to believe that a personhas committed a crime of genocide within the jurisdiction of the Court must be the only reasonable conclusion to be drawnfrom the evidence presented by the Prosecutor for an arrest warrant to be issued against the suspect of such crime.